2014
DOI: 10.1371/journal.pone.0097967
|View full text |Cite
|
Sign up to set email alerts
|

Serum Estradiol Levels Predict Survival and Acute Kidney Injury in Patients with Septic Shock- A Prospective Study

Abstract: Sex hormones have diverse immunomodulatory effects that may be involved in the pathogenesis of sepsis. However, the roles of serum sex hormones in predicting outcomes and the severity of organ dysfunction, especially acute kidney injury (AKI), in septic shock patients remains controversial. We prospectively enrolled 107 clinically diagnosed pneumonia-related septic shock patients and serum sex hormone levels were measured on the day of shock onset. The aim of the present study was to investigate the predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Table 1 depicts the strong association between increased serum estradiol and progesterone levels and 28-day mortality in patients suffering from pneumonia-related septic shock, whereas serum testosterone levels are not noticeably different between survivors and non-survivors after a 28-day follow-up [ 67 ]. A prospective clinical study of elderly men who were free of cardiovascular disease at the time of blood sample collection, revealed a significant inverse association between dehydrotestosterone (DHT) and calculated free DHT levels with all-cause mortality during a follow-up period of 9 years, whereas total testosterone and calculated free testosterone showed no significant correlation with mortality [ 68 ].…”
Section: Promising Metabolic Biomarkers For Prediction Of All-cause Mmentioning
confidence: 99%
“…Table 1 depicts the strong association between increased serum estradiol and progesterone levels and 28-day mortality in patients suffering from pneumonia-related septic shock, whereas serum testosterone levels are not noticeably different between survivors and non-survivors after a 28-day follow-up [ 67 ]. A prospective clinical study of elderly men who were free of cardiovascular disease at the time of blood sample collection, revealed a significant inverse association between dehydrotestosterone (DHT) and calculated free DHT levels with all-cause mortality during a follow-up period of 9 years, whereas total testosterone and calculated free testosterone showed no significant correlation with mortality [ 68 ].…”
Section: Promising Metabolic Biomarkers For Prediction Of All-cause Mmentioning
confidence: 99%
“…During stress, gonadal synthesis of estradiol is inhibited by Class I cytokines and tumor necrosis factor alpha, whereas there is an activation of the peripheral estradiol production by enzyme aromatase in adipose tissue, regardless of gender of the patients. [ 1 2 3 6 ] Estradiol causes changes in the immune response such as inhibition of the action of T-cells and activation of B-cell and macrophages inducing the production of interleukin 2 and interferon-α, mainly. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Different studies in animal models have shown that changes in the immune response induced by estradiol produce an inflammatory response and modify the survival. [ 3 5 6 7 8 ] In humans, some authors have shown that, in clinical settings such as trauma or surgical patients, the increase in the serum level of estradiol was associated with increased severity of disease and mortality, regardless of the gender of patients, and was proposed as a tool for predicting mortality. [ 1 3 5 8 9 10 ] All this evidence has been documented in specific groups of patients and used different cutoffs of serum estradiol levels to predict mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous adrenocortical function is of prognostic value in critical illness and sepsis [714], of which community-acquired pneumonia (CAP) is a major source [15–17]. Morbidity in CAP is still high also, owing to higher risk for cardiovascular events [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity in CAP is still high also, owing to higher risk for cardiovascular events [18, 19]. Researchers in multiple studies have investigated the adrenal steroid metabolism in relation to CAP-associated outcomes [14, 2025]. In observational trials, researchers have reported increased admission cortisol levels to be independent predictors of disease severity and short-term mortality in patients across the spectrum of mild to severe CAP [2024].…”
Section: Introductionmentioning
confidence: 99%